Functional red palm oil as a fish oil alternative on growth, feed utilization, and coloration in giant freshwater prawn Macrobrachium rosenbergii - Teoh, Chaiw-Yee; Johnson, Wong Xiu Yang; Pit, Sze Liew (Penerbit Universiti Kebangsaan Malaysia, 2025)
Functional red palm oil (FRPO), rich in bioactive compounds, enhances digestion, metabolism, immune function, and coloration in aquatic species. Given Malaysia’s robust palm oil industry, investigating FRPO as a sustainable, locally-sourced lipid alternative for aquaculture industry is essential. A 32-day feeding trial was conducted to evaluate the effects of substituting dietary fish oil (FO) with FRPO on growth performance, survival rate, coloration and feed utilization of giant freshwater prawn (GFP), Macrobrachium rosenbergii. Three experimental diets were formulated to contain different lipid sources: Diet 1 (100% of FO), Diet 2 (50% FO + 50% FRPO), and Diet 3 (100% of FRPO). A total of 180 prawns with average weight of 0.35 g were assigned into nine tanks and fed twice daily to satiation. Results showed that prawns fed with Diet 2 had significantly (p < 0.05) better feed conversion ratio, specific growth rate, percentage weight gain and final weight than other two groups. However, no significant (p > 0.05) difference was observed in the survival rate of the experimental prawns. All prawns showed significant differences in lightness (L*), while those fed Diet 3 showing significantly higher redness (a*) compared to the other groups. It is evident that a 50% inclusion of FRPO can enhance pellet palatability, significantly boost growth performance, feed utilization, and coloration in GFP. These findings suggest that FRPO is a viable, sustainable alternative to FO, advancing the development of aquafeeds with local ingredients.